A new method for measuring meander parameters. The lower Jiu river case study, Romania (Geo-Eco-Marina, 2023)
The study of river channel dynamics at different time intervals is an element of interest in river geomorphology because it provides qualitative and quantitative information related to the river style and patterns of evolution. Old maps represent archives of extremely valuable information related to the natural and human environment, which provide the necessary data for such studies. This paper uses data from old maps to analyze the evolution of the Jiu River between 1857 and 2021. A new method for measuring meander parameters has been developed and may be applied to any type of river channel. The calculation and analysis of the parameters (sinuosity coefficient, length, amplitude, type, and shape) for each riverbed section led to the identification of distinct evolutionary patterns which were discussed in relation to control factors. We concluded that the Jiu river channel gradually straightened during the last 164 years due to upstream anthropogenic interventions such as dams and hydrotechnical works which reduced the natural riverbed dynamicsreflected in low sinuosity and meandering levels.
Keywords: diachronic analysis; river dynamics; fluvial geomorphology; anthropogenic impact; geomorphological evolution; Jiu-Danube confluence